An International Perspective on Chronic Multimorbidity: Approaching the Elephant in the Room. (16th September 2017) - Vetrano, Davide L; Calderón-Larrañaga, Amaia; Marengoni, Alessandra; Onder, Graziano; Bauer, Jürgen M; Cesari, Matteo; Ferrucci, Luigi; Fratiglioni, Laura
Abstract: Multimorbidity is a common and burdensome condition that may affect quality of life, increase medical needs, and make people live more years of life with disability. Negative outcomes related to multimorbidity occur beyond what we would expect from the summed effect of single conditions, as chronic diseases interact with each other, mutually enhancing their negative effects, and eventually leading to new clinical phenotypes. Moreover, multimorbidity mirrors an accelerated global susceptibility and a loss of resilience, which are both hallmarks of aging. Due to the complexity of its assessment and definition, and the lack of clear evidence steering its management, multimorbidity represents one of the main current challenges for clinicians, researchers, and policymakers. The authors of this article recently reflected on these issues during two twin international symposia at the 2016 European Union Geriatric Medicine Society (EUGMS) meeting in Lisbon, Portugal, and the 2016 Gerontological Society of America (GSA) meeting in New Orleans, USA. The present work summarizes the most relevant aspects related to multimorbidity, with the ultimate goal to identify knowledge gaps and suggest future directions to approach this condition.